Accounting for Price Changes: American Steel Rails, 1879-1910 - Allen, Robert C. (Journal of Political Economy, 1981)
A framework is developed for decomposing product price changes into changes in input prices, technical efficiency, and deviations of price from unit cost. This framework facilitates the measurement of productivity growth in noncompetitive industries. The history of American steel rail prices between 1879 and 1910 is analyzed, and it is concluded (in contrast with much recent work) that productivity growth remained rapid until the twentieth century and that the steel industry was sufficiently collusive so that the rail producers received the benefits of that productivity growth as excess profits.